Efeito da fermentação da cama de frango reutilizada sobre o desempenho, ambiência e a qualidade físico-química da cama de frangos de corte - Rocha, Priscila Almeida dos Santos da (2017)
The flat fermentation in chicken litter is a variation of the fermentative process in washers and consists in, after the exit of the birds, to moisten the chicken litter and then to cover it with canvas, that must be well placed in all extension of the aviary to prevent air from entering between the chicken litter and the tarp. In the light of the above, the aim of chapter 1 was to analyze the main factors that affect the thermal comfort of the birds and the quality of the chicken litter, as well as the alternatives used as treatment of the chicken litter to ensure its reuse. In chapter 2, the objective of this study was to evaluate the effect of heat treatment on reused chicken litter on broiler chickens performance, ambience and physical-chemical quality of broiler litter, in the northern region of the State of Mato Grosso. Two experimental aviaries were used with 60 birds housed in each aviary, totaling 120 broilers mixed in each lot, considering density of 13 birds / m2. One of the aviaries was used to ferment with tarpaulin as a litter treatment, and in the other aviary the chicken litter received not any one kind of treatment, and it remained spread throughout the extension of the aviary, this processes occurred after the broilers were slaughtered at 42 days of age. The performance variables evaluated were feed intake, weight gain, feed conversion and live weight. The ambience was evaluated through the variables of ambient temperature, relative air humidity, black globe temperature, wind speed and ammonia concentration in bed and at bird height. The physical-chemical quality of the bed was evaluated through the variables of temperature and maximum, minimum and momentary humidity of the chicken litter, deep chicken litter temperature, pH and ammonia of the chicken litter. There was a significant effect on feed intake, weight gain and feed conversion for the weeks of the analyzed poultry, regardless of the treatment of the chicken litter used. Ammonia at bed and bird height and wind speed had a significant effect on the comparisons between bird life weeks. The pH of the litter showed difference between the lots after the fermentation treatment. It was concluded that the heat treatment of flat chicken litter fermentation with cover made by plastic canvas presented satisfactory results, because it did not affect the performance of the birds.